Elizabethkingia meningoseptica –An emerging infection: A case report - Favas, K; Bindu, A (Indian Journal of Child Health, 2021)
Elizabethkingia meningoseptica are Gram-negative rod bacteria that are commonly found in the environment. The bacteria have also been associated with nosocomial infections, having been isolated on contaminated medical equipment, especially in neonatal wards. Rapid diagnosis and early institution of appropriate therapy for prolonged period are essential for the management of such infections. Here, we report a case of bacteremia due to E. meningoseptica in a neonate who was presented with respiratory distress and seizure episodes. A diagnosis of bacterial meningitis was made based on clinical findings and examination of cerebrospinal fluid. The baby was treated with antibiotics and other supportive measures, that helped to improve the condition. During follow-up, the baby showed developmental delay with hydrocephalus. E. meningoseptica can cause severe infection, with high risk of mortality and neurological sequelae in neonates. Intensive care and multidisciplinary interventions are crucial for the case management. Awareness among clinicians along with correct diagnosis in microbiology laboratory is required to minimize the fatal outcome associated with this infection.